Education & Training of Peon on Infection Control: Experience in Peripheral Health Facilities in Nepal - Gurung, Gagan (International Journal of Infection Control, 2009)
Infectious diseases are consistently in transition with new diseases develop and known diseases become widespread or reemerge. Infection control is crucial for the safety of health workers, others working in health care settings, individuals and communities receiving health care. Peons are responsible for conducting the majority of procedures directly related to blood and bodily secretions making them the most vulnerable group for infection. Yet they have rarely been included in any education concerning Infection control. This was before-after study designed to assess the effectiveness of training of peons to improve Infection control at the peripheral health facilities of Nepal. A total of 33 health facilities were selected using random sampling for the study. It was found that after the training intervention, health facilities with functioning Infection control practice was increased significantly. Environmental cleanliness was increased from 24% to 52%. Similarly, hand washing practice was increased from 36% to 88%. The waste disposal practice was increased from 27% to 52%. Decontamination was increased from 21% to 45%. It can be concluded that training and coaching of peon to improve the infection control practice in the peripheral health facilities was found very effective. It is recommended to train the peons on infection control using low-tech approaches that are practical and simple, to improve Infection control at the peripheral health facilities. Key words: Infection Control, Hand Washing, Waste Disposal, Decontamination, Training, Peons.